From immersive worlds to virtual showrooms: a taxonomy of virtual reality shopping applications - Elsholz, Sophia; Korbel, Jakob Johannes; Pham, Kevin; Zarnekow, Rüdiger (Frontiers in Virtual Reality, 2025)
The advent of virtual reality (VR) technology and the utilization of electronic commerce (e-commerce) have become prominent features of the contemporary landscape with anticipated growth in the future. Consequently, the concept of shopping in VR has been subject of extensive research, with first consumer applications being now available on the market. The objective of this paper is to create a taxonomy for VR shopping applications, with the intention of providing a framework for the categorization of applications, as well as insights into current market developments. The taxonomy is derived from the findings of a literature review, including 55 studies, and the evaluation of 13 commercial applications. A comparison of research and commercial applications reveals that while research has advanced, commercial applications are predominantly showrooms without purchase possibilities. This discrepancy offers potential avenues for future research to understand the factors influencing companies’ reluctance to develop and adopt VR shopping applications.